Mulching, plant population density and indigenous knowledge of wild ginger (Siphonochilus Aethiopicus) - Soundy, Puffy (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Plant Production: Agronomy))--University of Pretoria, 2007.